The role of circulating lipid chaperone proteins in insulin signalling and inflammation - Mohd Radzuan, Hazulin; Cole, Mark; Bennett, Andrew J. (2016)
A growing body of evidence indicates that adipose tissue actively secretes lipid binding proteins (LBPs) into circulatory system as paracrine signalling molecules. Among them, fatty acid binding protein 4 (FABP4) and lipocalin 2 (LCN2) have been implicated in the pathogenesis of obesity-induced insulin resistance (Krušinová & Pelikánová, 2008, Yan et al., 2007). FABP4 is thought to increase insulin resistance in obesity whereas the role of LCN2 is less clear being described as causing insulin resistance or sensitization in different model systems. We have examined the effects of varying glucose concentrations in normoxic and hypoxic conditions which mimic normal and obese/diabetic condition upon FABP4 and LCN2 expression and secretion in primary adipocytes. Secretion of LBPs has also been reported to be stimulated by calcium in adipocytes. Hence, we have examined the roles of the transient receptor vanilloid channels, TRPV1 and TRPV4, both of which transport calcium and have been implicated in adipose tissue insulin resistance, in FABP4 and LCN2 secretion (Zhang et al., 2007, Ye et al., 2012).